Hubungan Antara Tindak Pidana Korupsi Dan Kerugian Ekonomi Negara - Harly Clifford Jonas Salmon (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
Corruption in the public sector harms the economy and public welfare, especially in the management of the state budget and basic services. Misuse of public funds hampers the development of infrastructure, education, health, and creates sharp social inequalities. Corruption also undermines public trust in government, lowers productivity and the country's competitiveness, which slows economic growth and increases poverty. In economic criminal law, corruption is specifically regulated in Law No. 31 of 1999. This research aims to examine the relationship between the crime of corruption and its impact on state economic losses from the perspective of economic criminal law. This research uses normative juridical method with statute approach and literature data collection. Data sources include primary legal materials (1945 Constitution, Law No. 31/1999, Emergency Law No. 7/1955), secondary (journals, books, scientific works), and tertiary (news articles, encyclopedia). The analysis was conducted using content analysis. Corruption has a significant impact on state economic losses through abuse of power, bribery, embezzlement and collusion. Corruption inhibits investment, slows economic growth, increases unemployment, and triggers poverty. Law No. 31/1999 regulates sanctions for actions that harm the state's finances and economy Its far-reaching impacts include budget wastage, poor quality of public services, and inefficient use of resources. Distrust in government due to corruption also discourages foreign investment. Eradicating corruption is therefore key to promoting sustainable development and improving the country's overall economy.